Evaluation of Liquefaction Potential based on Cone Penetration Test (CPT) and Semi-empirical Methods - Fatima Ezzahraa Latifi; Khadija Baba; Ghizlan Ardouz; Latifa EL Bouanani (Salehan Institute of Higher Education, 2023)
The phenomenon of soil liquefaction can be an induced effect of earthquake shaking where the saturated soil loses some or all of its bearing capacity and stiffness. Likewise, the increase of water pressure in the soil pores under the seismic wave causes a decrease of the shear strength. As a result, the soil becomes liquefied and susceptible to producing permanent deformations. The phenomenon of liquefaction is generally unpredictable, and neglecting it can influence the stability of structures and infrastructure foundations. Since the 1964 Alaska and Niigata earthquakes, more research works have been conducted to assess land liquefaction vulnerability. This study is undertaken in this field, whose objective, on the one hand, is to signal the phenomenon of liquefaction in the north of Morocco as a geo-technical part known for its instability and, on the other hand, to study the semi-empirical methods to adequately evaluate the liquefaction potential while specifying the most appropriate method for our case study. Similarly, the study is based on data derived from experimental results of in-situ tests applied to the embankment crossing the valley of